COMPARISON OF GENEXPERT® PROBE MISSING IN HOTSPOT RRDR OF RPOB GENE AMONG PRIMARY AND ACQUIRED DRUG RESISTANT CASES OF PULMONARY TUBERCULOSIS - MUNIR, MK; SHAMIM, S; REHMAN, S; HANIF, A; SAEED, MS (Biological and Clinical Sciences Research Journal, 2022)
There are differences in probe pattern missing in rifampicin resistance determining region of rpoB gene among primary and acquired resistant TB cases. This study aimed to observe the Xpert® MTB RIF Assay presenting probe missing in Hotspot RRDR of rpoB Gene among primary and acquired drug-resistant cases of pulmonary tuberculosis in a tertiary care setting of Lahore. This comparative cross-sectional work was undertaken at The University of Lahore in cooperation with the Department of Pulmonology and HRI-NIH TB Research Centre KEMU Lahore. Confirmed TB patients being sent for Xpert® MTB RIF Assay were the target population in this study. Based on previous TB treatment history, patients were divided into primary and acquired drug-resistant TB cases. Samples were subjected to Xpert® MTB RIF Assay, and any probes missing, i.e., probes A, B, C, D or E, were observed. Data from a total of 170 cases were finalized for analysis consisting of 84(49.4%) acquired TB cases and 86(50.6%) primary TB cases. A total of 90(52.9%) male and 80(47.1%) females were enrolled. The mean age of patients was 35.45±16.11 years. The proportion of missing probe E (78.2%) remained at the topmost, followed by none of the probes missing at 8.3%, probe A at 5.3%, probe C at 3.5%, probe B at 2.9% and probe D at 1.8%. There are variations in frequencies of probe missing in RDRR regions of rpoB genes among rifampicin-resistant cases of primary and acquired TB. A high frequency of no missing probes among primary resistant was found.